Central visual, acoustic, and motor pathway involvement in a Charcot-Marie-Tooth family with an Asn205Ser mutation in the connexin 32 gene. Issue 2 (1st February 1999) - Bähr, M; Andres, F; Timmerman, V; Nelis, M E; Van Broeckhoven, C; Dichgans, J
Abstract : BACKGROUND: X linked dominant Charcot-Marie-Tooth disease (CMT1X) is an inherited motor and sensory neuropathy that mainly affects the peripheral nervous system. CMT1X is associated with mutations in the gap junction protein connexin 32 (Cx32). Cx32 is expressed in Schwann cells and oligodendrocytes in the peripheral (PNS) and in the (CNS) respectively. METHODS: A CMT1X family with a Cx32 mutation was examined clinically and electrophysiologically to determine whether PNS, or CNS, or both pathways were affected. RESULTS: In a CMT1X family a novel mutation (Asn205Ser) was found in the fourth transmembrane domain of Cx32. The patients showed typical clinical and electrophysiological abnormalities in the PNS, but in addition visual, acoustic, and motor pathways of the CNS were affected subclinically. This was indicated by pathological changes in visually evoked potentials (VEPs), brainstem auditory evoked potentials (BAEPs), and central motor evoked potentials (CMEPs). CONCLUSIONS: These findings underscore the necessity of a careful analysis of CNS pathways in patients with CMT and Cx32 mutations. Abnormal electrophysiological findings in CNS pathway examinations should raise the suspicion of CMTX and a search for gene mutations towards Cx32 should be considered.